Has the assessment of isolated ankle injuries altered since 1993?. Issue 12 (18th November 2005) - Locker, T; Tryfonidis, M; Mason, S
Abstract : Background: Performance of emergency departments in England and Wales has declined in recent years. Data from the authors' department has shown that junior doctors now see fewer patients and spend longer over their assessment than was the case previously. This study aimed to determine how the assessment of patients with isolated ankle injuries changed over an 11 year period. Methods: A retrospective case note review was conducted. Data regarding the duration of assessment, clinical information recorded, investigations, and treatments were retrieved. Results: During the period studied 13 555 patients presented with isolated ankle injuries; case notes of 550 of these patients were reviewed in the present study. Linear regression demonstrated that the median length of time from arrival in the department until seen by a clinician increased ( b  = 3.0 min/year, 95% CI 0.7 to 5.2, p = 0.015), but the median length of time from seeing a clinician until leaving the department was unchanged ( b  = 0.6 min/year, 95% CI −1.3 to 2.5, p = 0.475). More clinical information was being recorded, but the proportion of patients having radiographs of the ankle ( b  = 0.24% per year, 95% CI −1.40% to 1.87%, p = 0.751) or in whom a fracture was diagnosed ( b  = −0.20% per year, 95% CI −1.59% to 1.19% per year, p = 0.752) remained unchanged. Conclusion: It appears from this study that the duration of assessment of patients with minor injuries is not changing although this result should be interpreted cautiously.